2000
DOI: 10.1007/pl00005511
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of sinigrin by methanol/ammonia/water treatment in model systems and mustard (Brassica nigra L.) seed meal

Abstract: Sinigrin (allylglucosinolate) was stored at 20 7C, 40 7C, and 60 7C in solutions containing 10% ammonia in 95% methanol (CH 3 OH/NH 3 /H 2 O). The individual samples were analyzed for their contents of sinigrin, its decomposition product allyl isothiocyanate (AITC) and other reaction products. The major reaction products were allyl thiourea, methyl ester of Nallyl thiocarbamoyl acid and allyl cyanide. A newly identified decomposition product of sinigrin was ethylcyanide. Defatted Brassica nigra seed meal was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is known that the presence of glucosinolates in Brassica seeds hampers the exploitation of the corresponding meals as fodders, because the glucosinolates can hydrolyze to a variety of products, including nitriles and isothiocyanates, some of which are potentially toxic 19. It has been reported that various isothiocyanates and cyanides can be formed from the allylglucosinolate sinigrin, which is naturally present in mustard seeds ( Brassica species) 20. During the oil pre‐pressing, the glucosinolates are staying in the rapeseed meal.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the presence of glucosinolates in Brassica seeds hampers the exploitation of the corresponding meals as fodders, because the glucosinolates can hydrolyze to a variety of products, including nitriles and isothiocyanates, some of which are potentially toxic 19. It has been reported that various isothiocyanates and cyanides can be formed from the allylglucosinolate sinigrin, which is naturally present in mustard seeds ( Brassica species) 20. During the oil pre‐pressing, the glucosinolates are staying in the rapeseed meal.…”
Section: Resultsmentioning
confidence: 99%
“…Under neutral pH, AITC is generally being produced in mustard seeds. The pungent odor of crushed mustard seeds can be attributed to the release of AITC from sinigrin, which is otherwise odorless before the enzymatic hydrolysis reaction (Pechácek and others ; Tsao and others ; Luciano and Holley ).…”
Section: Introductionmentioning
confidence: 99%